Reduction of Testicular Volume of Albino Rats in Lead Induced Toxicity and Reversal of IT with High Dosages of Vitamin C (Medical Forum Monthly, 2024)
Objective: Lead toxicity is a common industrial hazard. It affects all systems of the body. The study was conducted to see reduction in volume of the testes of albino rats and reversal of it with high dosages of vitamin C.Study Design: Experimental studyPlace and Duration of Study: The study was conducted in the Department of Anatomy, Post Graduate Medical Institute (PGMI), Lahore from May 2007 to April 2009.Materials and Methods: 90 albino rats were divided into five groups A, B, C, D and E. Each group was comprised of 18 animals and divided into 3 subgroups 1, 2 and 3 sacrificed after 5th, 6th and 7th weeks. Groups A was given normal saline, group B was given lead acetate 10mg/kg body weight, group C was given lead acetate with 250mg/kg body weight of vitamin C, group D was given lead acetate with vitamin C 500mg/kg body weight and group E was given vitamin C 1000mg/kg body weight with lead acetate intraperitoneally.Results: The animals sacrificed after the 5th week in subgroups A1, B1, C1, D1 and E1 showed insignificant changes while in subgroup A2, B2, C2, D2 and E2 sacrificed after 6th week, P value was 0.015 which was significant. The P value of subgroup 3 sacrificed after 7th week was 0.002 which was significant.Conclusion: This study showed that lead toxicity brought caused a significant reduction in the volume of the testes. The testes regained their normal size after heavy dosage of vitamin C.